PRODUCT QUALITY, PRICE, AND BRAND IMAGE ON VIVO SMARTPHONE PURCHASE INTENTION IN SURABAYA - Rohmansyah, Vicky; Suryawirawan, Okto Aditya (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This research aims to analyze the influence of product quality, price, and brand image on interest in buying Vivo smartphones in Surabaya. The object used in this study is the people of Surabaya who have used or used Vivo smartphones. This type of research is categorized as descriptive analysis research using a quantitative method approach. The research sample used in the study was 100 respondents who had purchased a Vivo Smartphone. This sampling technique uses a technique, namely the accidental sampling method, which is a method of determining a sample by taking respondents who coincidentally exist or are available somewhere according to the research context. Data was collected through a Google questionnaire form. The analytical method used in this study is Partial Least Square using SmartPLS 3.0 software. The results showed that product quality had a positive and significant effect on purchase intention, price had a positive and significant effect on purchase intention, then brand image had a positive and significant effect on purchase intention.